2010
DOI: 10.1007/s00441-010-1085-2
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional reprogramming of mouse embryonic stem cell/fibroblast hybrid cells is initiated at the heterokaryon stage

Abstract: Immunofluorescent analysis of markers specific for parental genomes was used to study heterokaryons and hybrid cells soon after the fusion of diploid embryonic stem (ES) cells marked with green fluorescent protein and diploid fibroblasts labeled by blue fluorescent beads. Heterokaryons were identified by an analysis of parental mitochondrial DNAs. Within 20 h after fusion, most heterokaryons (up to 80%) had a fibroblast-like phenotype, being positive for typical fibroblast markers (collagen type I, fibronectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…Experiments with hybrid cells conducted by Blau et al 25 suggested the possibility of broad epigenetic changes at a quiescent heterokaryon stage. In agreement with this, we 26 and others 27 have shown that the molecular changes that determine the success and direction (or dominance) of reprogramming occur during the first hours after cell fusion, even before the first cell division.…”
Section: Discussionsupporting
confidence: 88%
“…Experiments with hybrid cells conducted by Blau et al 25 suggested the possibility of broad epigenetic changes at a quiescent heterokaryon stage. In agreement with this, we 26 and others 27 have shown that the molecular changes that determine the success and direction (or dominance) of reprogramming occur during the first hours after cell fusion, even before the first cell division.…”
Section: Discussionsupporting
confidence: 88%
“…Immunofluorescence analysis was carried out according to previously published protocol [ 47 ]. In short, cells cultured on glass coverslips were fixed with 3% formaldehyde (Fluka, Germany) and permeabilized with 0.1% Triton X-100 (Fluka, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…All three cell types are reasonably pluripotent as judged by EB formation (this study) and other research (Ambrosi et al, 2007;Battulin et al, 2012;Gridina and Serov, 2010). FMRCs performed well in EB differentiation, but are not as pluripotent as the other two cell types because FMRCs cannot yield mice by tetraploid embryo complementation, although they can contribute to chimeras (Battulin et al, 2012).…”
mentioning
confidence: 91%